Determining Strategies for Improving Lltt Business Performance with Inequal (Internal Quality) and Servqual (Service Quality) Analysis Case Study: Deli Serdang, North Sumatera) - Clarita Bangun; Muhammad Sonny Abfertiawan (Budapest International Research and Critics University, 2022)
Currently, the Government has set the 2020-2024 RPJMN to achieve proper and safe access to sanitation (Domestic Wastewater) by 90% to reduce maternal mortality and stunting. In Deli Serdang Regency, the population's access to proper and safe sanitation facilities still needs improvement. Based on City/District Sanitation Strategy Update Document Data. In 2016, it was found that 158,462 residents did not have proper sanitation facilities, 95,077 residents performed open defecation and 25,750 residents disposed of wastewater directly into drainage channels. One of the Government's efforts to achieve the goal of safe sanitation is to implement the Scheduled Sludge Service (LLTT) system, which is a program that connects septic tanks to IPLT. This study aims to identify the dominant factors that affect business performance seen from the INTQUAL dimension from the manager's perspective, namely technical aspects, NSPK aspects, financial aspects, institutional aspects and public relations aspects, and SERVQUAL in terms of LLTT customers seen from the reliability aspect, tangibility, responsiveness, assurance, empathy. This study was conducted to investigate the suitability of the LLTT practice of 78 managers and 78 customers using the purposive sampling technique. The questionnaire results were then analyzed using the Structural Equation Modeling method with SPSS and AMOS. It was found that the model formed had fulfilled the goodness of fit, and it was also found that INTQUAL had a statistically significant effect on Business Performance. The recommendations are focused on the manager or executor, namely by implementing a product characterization strategy, namely product/service engineering strategy, pricing strategy and ease of payment, Development and Marketing Strategy, and Promotion Strategy.